Developing Historical Competency: Teaching German History Through History Films At University Putra Malaysia (BA German Programme) - Schaar, Torsten (2022)
History films personalize, dramatize and emotionalize historical events and characters. They revive the past by exemplifying it in the present, engage ongoing discourses of history and as a result have proven to be the most influential medium in conveying history to large audiences. History films are regarded as an attractive, motivating and efficient (supplementary) teaching and learning medium in history as well as in foreign language classes. As part of the course “Historical Survey of Germany” (BA German-programme at University Putra Malaysia) history film projects on important periods and events in German history were conducted. The article introduces a film project on World War II and describes the pedagogical approach which aims to develop three core competencies of historical understanding – Content Knowledge, Historical Empathy/Perspective Recognition and Narrative Analysis. It discusses selected general findings provided as qualitative data in group and individual assignments. While the responses to questions related to Content Knowledge and Narrative Analysis show that students achieved higher competency levels, the participants showed shortcomings in the rational examination of historical characters, their perspectives and motivations for their actions. Time, practice and guidance can be identified as key factors in developing historical literacy competencies further.